The Characteristic Of Geographical And Socio-Economic Conditions Of Farmers In Peatland Rasau Jaya Tiga Village - Hayatullah, Addin Nur; Ulfah, Maria; Adlika, Nur Meily; Asriati, Nuraini (Universitas Tanjungpura, 2024)
This study aims to determine the characteristics of the geographical conditions and socio-economic conditions of farmers in the peatlands of Rasau Jaya Tiga Village. This research uses mixed-method research with a sequential explanatory design approach. Geographical condition data were processed using spatial pattern analysis which was tested for accuracy using area sampling techniques. Data collection on the socio-economic conditions of peatland farmers was followed by qualitative steps and procedures with three classifications of peatland farmers as participants. The results showed that the characteristics of the soil types in the village of Rasau Jaya Tiga were dominated by organosol soils, with rainfall of 2,001